Silaturrahim Perspektif Filsafat Islam (Ontologi, Epistemologi, Aksiologi) - M. Dzikrul Hakim Al Ghozali (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2016)
Gathering(silaturrahim) in a language derived from two words namely silah (relationship) and Rahim (Rahim women) that have meaning nasab Relations, as the verse above says al-Arham (womb) is defined as the gathering(silaturrahim). But in essence the relationship is not just a relationship nasab, but further than that relationships among Muslims is part of silaturrahmi, so God mengibarat the Muslims like one body. As the word of God.